Effect of Side-Chain Variation on Single-Crystalline Structures for Revealing the Structure–Property Relationships of Organic Solar Cells - Yang, Chen; Yuan, Liu; Zhou, Ruimin; Wang, Zhen; Zhang, Jianqi; Zhang, Yajie; Lu, Kun; Wei, Zhixiang (Organic Materials, 2020)
The molecular stacking assembly in the active layer plays a significant role in the photovoltaic performance of organic solar cells (OSCs). Here, we report two new small molecular donors with different side chains, FBT-O and FBT-H, and their corresponding fullerene-based OSCs. A slight change in the side chains led to a big difference in the power conversion efficiencies (PCEs). Although the molecular structures of the two donors are similar to each other, PCEs of the devices based on FBT-O were almost three times higher than those of the devices based on FBT-H, with manifold short-circuit current density, fill factor, as well as three orders of magnitude enhancement in the hole mobility. The difference in their single crystal structures was thoroughly investigated, whereby the FBT-O exhibited better planarity leading to appropriate phase separation and domain size. Furthermore, two-dimensional grazing-incidence wide-angle X-ray scattering results of the blend films revealed that the two donors retained a similar stacking structure as compared to the single-crystal structures, thus, establishing a clear relationship between the molecular stacking structure and the device performance.
Keywords: side-chain modification; molecular stacking structure; hole mobility; single crystal